2020
DOI: 10.1177/0883073820931970
|View full text |Cite
|
Sign up to set email alerts
|

Evoked Potentials During Peripheral Stimulation Confirm Electrode Location in Thalamic Subnuclei in Children With Secondary Dystonia

Abstract: Deep brain stimulation is an elective surgical intervention that improves the function and quality of life in children with dystonia and other movement disorders. Both basal ganglia and thalamic nuclei have been found to be relevant targets for treatment of dystonia in children, including the ventral intermediate nucleus of the thalamus, in which stimulation can control dystonic spasms. Electrophysiological confirmation of correct electrode location within the ventralis intermediate nucleus is thus important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Although variations in subjects’ anatomy was expected due to differences in underlying pathology, in all cases targeting performed using the Schaltenbrand-Wahren atlas aligned and scaled to the patient's AC-PC line appeared to identify appropriate targets, confirmed by 2 neurosurgeons. We have previously confirmed that this atlas adequately identifies the Vim/Vo boundary in thalamus 23…”
Section: Methodssupporting
confidence: 68%
“…Although variations in subjects’ anatomy was expected due to differences in underlying pathology, in all cases targeting performed using the Schaltenbrand-Wahren atlas aligned and scaled to the patient's AC-PC line appeared to identify appropriate targets, confirmed by 2 neurosurgeons. We have previously confirmed that this atlas adequately identifies the Vim/Vo boundary in thalamus 23…”
Section: Methodssupporting
confidence: 68%
“…This resulted in approximately 1000 segments per stimulus location, which were finally averaged to increase signal-to-noise ratio [50]. The stimulus-triggered averaging methodology presented by Sinclair et al [50] was repeated for both sets of polarity reversed stimulation settings, which were finally aligned to produce a polarity-reversed average with smaller stimulus and decay artifacts [42, 51, 52], as shown in Figure 2 4 .…”
Section: Methodsmentioning
confidence: 99%
“…[3]. The position of leads and electrode contacts was determined by alignment of a post-operative computed tomography (CT) scan with the preoperative magnetic resonance image (MRI) detailed anatomic scan [21]. Each implanted lead contains 6 low-impedance (1-2 kΩ) ring macro-contacts with 2 mm height and 5 mm on-center spacing, as well as 10 high-impedance (70-90 kΩ) microwire electrodes (50-µm diameter) referred to as micro-contacts.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrode location was confirmed by co-registration of preoperative magnetic resonance imaging (MRI) and postoperative computed tomography (CT) scans. Thalamic targeting was confirmed by identification of leads in subnuclei known to have greater or lesser response to median nerve electrical stimulation (9).…”
Section: Surgical Proceduresmentioning
confidence: 97%